On the equivalence of pathwise mild and weak solutions for quasilinear SPDEs. Issue 5 (3rd September 2021) - Dhariwal, Gaurav; Huber, Florian; Neamţu, Alexandra
Abstract: The main goal of this work is to relate weak and pathwise mild solutions for parabolic quasilinear stochastic partial differential equations (SPDEs). Extending in a suitable way techniques from the theory of nonautonomous semilinear SPDEs to the quasilinear case, we prove the equivalence of these two solution concepts.